DETERMINANTS OF CORPORATE CASH HOLDINGS DURING CRISIS PERIOD - Ita Devina Zhardi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to empirically analyze the determinants of cash holding in manufacturing companies within two specific industry sector in Indonesia: the Consumer Goods industry sector and Automotive sector in 2019-2021 period. The objective of the study is likely to understand the factors that influence the amount of cash that manufacturing companies in these sectors hold during a time of economic uncertainty and disruption. Cash holdings can serve as a buffer against financial distress, allowing companies to cover operational expenses, debt obligations, and investment opportunities, especially during times of crisis like the COVID-19 pandemic. The selected determinants include Firm Size, Leverage using Debt to Assets Ratio, Debt to Maturity Structure, and Probability of Financial Distress.This study took 134 data observations as a sample using purposive sampling technique. Hypothesis testing is done using multiple linear analysis using Eviews 12 software as a data processing. The results of this study concluded that Firm Size has no effect on Cash Holding, Big companies don’t need to hold a lot of cash because they are able to carry out business activities more efficiently which is more profitable. Leverage, which is calculated using the Debt to Asset Ratio, has a significant negative effect, with debt the company has an obligation to pay interest expenses and loan principal so that the cash owned by the company will be reduced to pay off these obligations. Debt to Maturity Structure has a significant negative effect on Cash Holding, when companies with a greater proportion of short-term debt will maintain higher cash to avoid the financial pressures faced if their loans fail to be extended. Probability of Financial Distress has a significant effect on cash holding, when companies face financial distress it will cause companies to hold more cash and vice versa.